Beyond Viral : How to Attract Customers, Promote your Brand, and Make Money with Online Video - Nalty, Kevin H. and Scott, David Meerman (Hoboken,New Jersey John Wiley & Sons, Inc, 2010)
BPromote your product using the most visceral form of social media-online video/b Learn how to create cost-effective videos, engage your customers, compel them to measurable behaviors (awareness, intent, and purchase), and sustain your brand online. iBeyond Viral/i gives you the tools and tricks to successfully use online video to reach your business goals.ulliAuthor Kevin Nalty is the only career marketer who doubles as one of the most-viewed YouTube comediansliForeword by veteran vlogger David Meerman ScottliFirst-hand case studies of leading brands include Microsoft, Starbucks, GE, MTV, Mentos, Holiday Inn, and Fox BroadcastingliLearn from the successes of top companies and startups as well as the pitfalls and mistakes many of them are making/ul Online video has huge potential, mostly untapped. Put your business at the forefront of this important medium with the proven methods described by iBeyond Viral/i.
Include Notes and Index
Keywords: Viral Marketing -- Internet Videos -- Business